2009
DOI: 10.1016/j.pneurobio.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of fetal brain renin–angiotensin system and hypertension programmed in fetal origins

Abstract: Since the concept of fetal origins of adult diseases was introduced in 1980s, the development of the renin-angiotensin system (RAS) in normal and abnormal patterns has attracted attention. Recent studies have shown the importance of the fetal RAS in both prenatal and postnatal development. This review focuses on the functional development of the fetal brain RAS, and ontogeny of local brain RAS components in utero. The central RAS plays an important role in the control of fetal cardiovascular responses, body fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 132 publications
0
30
0
Order By: Relevance
“…Both AT 1 R and AT 2 R have been suggested to be involved in cellular development, including cellular proliferation and differentiation [8,9,10,11,12,36]. In light of this, at least one explanation was considered for the data gained in the present study: an increase of fetal renal AT 1 R and a decrease of AT 2 R following hypoxia may contribute to cell growth, differentiation, migration and apoptosis [37,38] in the cortical zone of the fetal kidney and may be involved in alterations in glomerular and tubular histology. Although future studies are needed for further clarification, the present study was the first to demonstrate that the fetal renal AT 1 R/AT 2 R ratio was significantly increased following hypoxia in association with glomerular and tubular alterations in utero.…”
Section: Discussionmentioning
confidence: 80%
“…Both AT 1 R and AT 2 R have been suggested to be involved in cellular development, including cellular proliferation and differentiation [8,9,10,11,12,36]. In light of this, at least one explanation was considered for the data gained in the present study: an increase of fetal renal AT 1 R and a decrease of AT 2 R following hypoxia may contribute to cell growth, differentiation, migration and apoptosis [37,38] in the cortical zone of the fetal kidney and may be involved in alterations in glomerular and tubular histology. Although future studies are needed for further clarification, the present study was the first to demonstrate that the fetal renal AT 1 R/AT 2 R ratio was significantly increased following hypoxia in association with glomerular and tubular alterations in utero.…”
Section: Discussionmentioning
confidence: 80%
“…Cardiovascular functions of the RAS system are conserved in teleosts, and agt was similarly increased along with acute phase response genes in 24 hpf zebrafish exposed to mercury (Le Mevel et al , 2008; Ung et al , 2010). Though not yet explored in zebrafish embryos, the RAS system has been identified as important for fetal cardiovascular response, body fluid balance, and neuroendocrine regulation, and may be involved in fetal programming of hypertension later in life (Mao et al , 2009). …”
Section: Resultsmentioning
confidence: 99%
“…However, AT 1 :AT 2 mRNA and protein expression ratio in the offspring kidney was significantly increased. An absolute or relative increase of AT 1 may contribute to cell growth and apoptosis (Fitzsimons 1998, Mao et al 2009) in the kidney. The present study demonstrated that renal AT 1 /AT 2 could be significantly altered in the kidney by prenatal HSDs.…”
Section: Discussionmentioning
confidence: 99%